Mental Health Emergency Department Use among Treatment-Seeking Adults in a Rural Northern Appalachian Clinic: The Role of Homelessness and Alcohol Use. - Clarkson-Hendrix, Michael L; Heinen, Cassidy; Kearns, Kevin (Health & Social Work, 2026)
Emergency departments are vital safety-net resources for adults seeking mental health treatment. Frequent mental health emergency department use has been associated with homelessness and alcohol use. However, little of this research has been conducted in rural settings, particularly in Northern Appalachia. Therefore, this program-level study aimed to describe the relationship between recent mental health emergency department use, homelessness, and alcohol use in intake survey data from one outpatient mental health clinic. Participants were 1,293 adults seeking treatment between June 2020 and August 2022. On average, participants reported using an emergency room for a psychiatric or emotional problem less than one time in the past 30 days. Nights spent homeless were statistically significantly positively associated with recent mental health emergency department use. Additionally, those who used alcohol daily or almost daily demonstrated a statistically significant greater frequency of mental health emergency department use compared with adults who did not use alcohol within the past 30 days. Future social work research should replicate this study with a larger, multisite, random sample of mental health treatment–seeking adults in rural Northern Appalachian settings.